Eluvial chromite resources of the Great Dyke of Zimbabwe - Musa, Caston Tamburayi (Rhodes University, Faculty of Science, Department of Geology, 2007)
Apart from the concentrations of chromite in layers within the Great Dyke and other ultramafic complexes, chromite also occurs as interstitial grains throughout the olivine-bearing rock-types. These olivine-bearing rocks include no rites, gabbros, dunites and pyroxenites. Chromite concentration in these rocks varies from 0.48 to 3.09 per cent of the rock, usually in the form of chromite (Ahrens, 1965; Worst, 1960). A small fraction of this chromite settled to form chromitite layers whilst the remainder is retained within the rock mass as finely disseminated chromite and chromite interstitial to olivine. This retained chromite is much finer grained than layer chromite and is the primary source of eluvial chromite (Cotterill, 1981). During weathering of the serpentine rock and transportation by rainwater, the heavier chromite and magnetite grains are re-deposited along watercourses and vleis or valleys as the speed of the water is retarded sufficiently for the heavier particles to settle. The lighter serpentine material is removed and the chromite concentration in the soil is increased, thus resulting in eluvial chromite (Keech et ai, 1961; Worst, 1960; Prendergast, 1978). The concentration of chromite particles in soil can be up to 15 (or more) Crâ‚‚Oâ‚ƒ %, resulting in economic and exploitable deposits, located primarily along the Great Dyke fiacks. A preliminary evaluation of the eluvials indicate that the Great Dyke could be host to up to 10 million tonnes of potential chromite concentrates which could be processed from such eluvial concentrates. These chromite-rich soils can be mined more cheaply than the traditional seams mining and processed into chromite concentrates through simple mechanical processing techniques of spirals, jigs and heavy media separators. The resultant chromite concentrates are of high quality and can be used to manufacture chromite ore briquettes, which are an alternative to lumpy chromite smelter feed. The main challenges to eluvial mining are the inevitable environmental degradation and coming up with methods that could possibly mitigate against such environmental damage. The distribution of these eluvials over vast plains as thin soil horizons, necessitate use of mobile concentrator plants and hence establishment of extensive infrastructure. These challenges, however, are not insurmountable and test mining and previous production runs have proved profitable. The eluvials are also associated with some lateritic nickel concentrations. The nickel occurs in close association with some oxide such as goethite and garnierite and is associated with iron-manganiferous soil pisolites. The analyses of these pisolites indicate high nickel grades of generally above 1.00 %Ni. Such high nickel-content of Great Dyke laterites warrant, further investigations.
Keywords: Dikes (Geology) -- Zimbabwe; Chromite -- Zimbabwe; Geology -- Zimbabwe; Olivine; Serpentinite; Eluvium